THE PRISON SYSTEM IN VALPARAÍSO FROM 1836 TO 1842 THE STREET CARS AND MOVING CAGES ACCORDING TO DOCUMENTARY SOURCES - Monteverde Sánchez, Alessandro (2013)
The imposition of the rule of law at the beginning of the organization of the Chilean Republic meant the social control of some part of the population. To achieve that, the incorporation of street cars was planned as means of containment by the Minister Portales, considered the promoter of the national Chilean state. These were cages of limited capacity and they were moved by animals to different places in Valparaíso and the people in were exhibited to be confronted to public vengeance.